“We Fill in Our Working Understanding”: On Codes, Classifications and the Production of Accurate Data - Winthereik, B. R. (Methods of Information in Medicine, 2003)
Objectives: This paper describes differences in the way general practitioners in Denmark, The Netherlands and Great Britain make codes fit into the local conditions under which they work.Methods: An ethnographic study method has been used to collect data in Dutch, British and Danish general practices.Results and Conclusions: The paper argues that what counts as “accurate data” is locally constructed. As codes are produced in local networks of human and technological actors, the way accuracy is constructed is dependent on the extra work that is carried out (by actors inside the clinic as well as outside of it). On the basis of differences between coding practices and classification systems the paper discusses how inherent tensions between coding for primary and secondary purposes can be solved. The paper concludes that instead of evaluating data in terms of how accurate they are in general, they should be looked at in terms of pertinence to specific research questions.
Keywords: Diagnostic codes; classification systems; general practice; electronic patient record; localization; accuracy; ethnography